Epidemiology of injuries in National Collegiate Athletic Association men's soccer: 2014-2015 through 2018-2019 - Chandran, A.; Morris, S. N.; Boltz, A. J.; Robison, H. J.; Collins, C. L. (Journal of Athletic Training, 2021)
Context: The National Collegiate Athletic Association has sponsored men's soccer programs since 1959, and the popularity of the sport has grown over time. Background: Routine examinations of athlete injuries are important for identifying emerging temporal patterns. Methods: Exposure and injury data collected in the National Collegiate Athletic Association Injury Surveillance Program from 2014-2015 through 2018-2019 were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differential injury rates. Results: The overall injury rate was 8.51 per 1000 athlete exposures. Lateral ligament complex tears (ankle sprains) (9.2%), hamstring tears (7.0%), and concussions (5.2%) were the most commonly reported injuries. Rates of lateral ligament complex tears remained stable from 2014-2015 through 2018-2019, whereas hamstring tear rates decreased and concussion rates increased. Summary: The findings of this study were in line with the existing epidemiological evidence, although notable temporal patterns were observed. Incidence trajectories of commonly observed injuries warrant particular attention in the future.